Inhibitory effects of everolimus in combination with paclitaxel on adriamycin-resistant breast cancer cell line MDA-MB-231 - Tinghua Xu; Pengxi Liu; Qingming Li; Changbin Shi; Xinjie Wang (Elsevier, 2020)
Objective: We aimed to evaluate the therapeutic effects of paclitaxel in combination with mTOR inhibitor everolimus on adriamycin-resistant breast cancer cell line MDA-MB-231 (MDA-MB-231/ADR). Materials and methods: MDA-MB-231/ADR cells were treated with different concentrations of paclitaxel and everolimus. The IC50 values after 48 h of treatment were measured by the MTT assay. The apoptosis rate and cell cycle were detected by flow cytometry. The protein expressions of Akt, PI3K, mTOR, p-pI3K, p-AKT and p-mTOR were detected by Western blot. Results: When paclitaxel at ≥1.56 μg/ml was used, the growth of MDA-MB-231/ADR cells was inhibited more significantly than that of control group (P < 0.05). After treatment with ≥6.25 μg/ml everolimus, the cell growth was also suppressed more significantly (P < 0.05). The IC50 values of everolimus and paclitaxel were 32.50 μg/ml and 7.80 μg/ml, respectively. The inhibition rate of paclitaxel plus everolimus was significantly enhanced with increasing paclitaxel concentration (P < 0.001). After treatment with 7.80 μg/ml paclitaxel, the two drugs had best synergistic inhibitory effects on proliferation. Compared with drugs alone, the combination significantly promoted apoptosis (P < 0.001). The paclitaxel + everolimus group had significantly more cells in the G0-G1 phase than those of control and individual drug groups (P < 0.001). Everolimus significantly decreased mTOR and p-mTOR expressions compared with those of control group (P < 0.001). Compared with everolimus alone, the combination reduced the expressions more significantly (P < 0.05). Paclitaxel decreased the expression levels of PI3K, p-PI3K and p-AKT. Compared with paclitaxel alone, the combination significantly promoted the reduction of PI3K, p-PI3K and p-AKT expressions (P < 0.05). Conclusion: Everolimus can enhance the effect of paclitaxel on MDA-MB-231/ADR cells, inhibit cell proliferation, induce apoptosis and arrest cell cycle in the G1 phase mainly by down-regulating the expressions of key proteins in the mTOR signaling pathway.